Determinants of Saving Intentions in Islamic Current Accounts: Empirical Evidence from Muslim Community in Indonesia - Fitri, Resfa; Sutito, Yolanda M. M.; Irfany, Mohammad Iqbal (Islamic Economics Methodology, 2025)
The growth of current accounts is still far behind compared to savings and deposits. West Jakarta as the region with the highest Islamic bank assets still shows low DPK growth, especially in Islamic current accounts. This research aims to identify the characteristics of respondents and variables that affect the interest of Muslim communities in West Jakarta to save funds in Islamic current accounts. The method used is descriptive analysis and SEM-PLS analysis with the number of respondents involved in this study as many as 175 Muslims in West Jakarta. The results showed that the variables of attitude, reputation, behavioral control,.and subjective norms had a positive and significant influence, while profit sharing and product had a positive but insignificant effect, and the promotion variable has a negative and insignificant effect on the intention of West Jakarta Muslim Community saving funds in the Islamic current account.